Analisis Program Kip Kuliah dalam Mengatasi Inflasi Terhadap Kesenjangan Akses Pendidikan Tinggi - Elisabet Rahmani; Dewi Kusuma Wardani; Muhammad Sabandi (Jurnal Ekonomi dan Bisnis Digital, 2025)
Rising inflation impacts the cost of higher education in Indonesia, particularly through increases in the Tuition Fee, living costs, and academic support needs. This situation threatens equitable access to higher education, particularly for low-income communities. This study aims to analyze the impact of education costs on barriers for vulnerable communities to access higher education and examine the effectiveness of the Kartu Indonesia Pintar (KIP) College Program as a government effort to maintain educational equity amidst inflationary pressures. The method used is a literature study by reviewing various journals and policy reports related to the relationship between inflation, education financing, and the implementation of KIP College. The analysis results show that although KIP College is able to ease the burden on students and expand educational participation, challenges still arise in aspects of targeting accuracy, the nominal amount of assistance that has not been adjusted for inflation, and regional equity. Therefore, policy strengthening is needed through periodic adjustments to assistance, digitalization of fund management, and the establishment of affirmative quotas for underdeveloped regions so that KIP College can function more effectively as an instrument of social justice and a driver of human resource development.